Strategic Location Effectiveness Against Non-Muslim Customers Interest in Saving (Bank Syari’ah Indonesia Case Study DIY) - Panji Riski Kurniawan; Muslihun Muslihun (STKIP Taman Siswa Bima, 2024)
The presence of Bank Syari’ah Indonesia, represents the seriousness of the government's in paying attention to the development of Sharia-based services in Indonesia, with various problems and turbulent economic conditions. Determining the strategic location of a bank is the main thing to do by paying attention to some important indicators such as proximity to the city center, shopping malls, large areas such as parking lots and other signs. The study aims to test and analyze the influence of strategic location factors on the interests of non-Muslim customers of Shariah Bank Indonesia, located in Yogyakarta Special District. The population in this study is a non-Muslim DIY community. The data used in this research is primary data collected through questionnaires and interviews with respondents. A total of 120 non-Muslim respondents were in Yogyakarta Special District. The results of the study showed that, the location variable with T table of 0.154> T counts of -1,975 with a significant rate of 0.051. This indicates that the location does not have significant effectiveness in attracting non-Muslim interest to become a customer of Bank Syari’ah Indonesia in DIY. On the contrary, the promotion and product aspects have more significant efficiency to attract non-Muslim interest in becoming a client of Bank Islamic Syari'ah in DIY, with a variable T count of 4,320> T value table 0,154 with a significant rate of 0,000, and T table 0.154> T count 5, 306 with a signifying rate 0,000.